Фоностилистическое варьирование звучащей речи теледискурса Германии - Монастырская, Ю.Г. (Культура народов Причерноморья, 2013)
В статье рассматриваются проблемы фоностилистической вариативности реализации
консонантизма в иностранных словах (англицизмах и галлицизмах) в теледискурсе Германии,
представленного звучащей речью специально обученных нормам произносительного стандарта
дикторов и модераторов. На основе сопоставления прочтённой речи и подготовленного говорения
выявляются значительные противоречия между кодифицированной нормой, представленной новейшим
немецким орфоэпическим словарём, и речевой действительностью.
Ключевые слова: теледискурс, звучащая речь, произносительный стандарт, фоностилистическая
вариативность, англицизмы и галлицизмы. У статті розглядаються проблеми фоностилістичної варіативності реалізації
консонантизму в іноземних словах (англізмах та галіцизмах) у теледискурсі Німеччини, представленого
звучним мовленням спеціально навчених нормам вимовного стандарту дикторів і модераторів. На основі
зіставлення прочитаного мовлення і підготовленого говоріння виявляються значні суперечності між
кодифікованою нормою, представленої новітнім німецьким орфоепічних словником, і мовної дійсністю.
Ключові слова: теледискурс, звучне мовлення, мовний стандарт, фоностилістична варіативність,
англізми та галіцізми. The article stipulates the problems of phonostylistic variations of consonantism in foreign words
(Anglicisms and Gallicisms) in TV discourse of Germany represented by the speech of announcers and
moderators (ZDF, ARD, DW-tv), who were specially trained to the norms of pronounciation standards. It
concerns the problem of the realization of consonants by germanizing the foreign words from
English and French, which are the most frequent in the German mass media language. Wide variety of the
implementation of the consonants is revealed either in the codified norm represented by the newest German
orthoepic dictionary or in the real norm, which is produced by professional German TV announcers because of
different degrees of the phonetic germanizing of Anglicisms and Gallicisms. In comparison of the speech reality
(read speech and prepared speaking) with the codified norm deviations have been found in the application of
consonants.
Keywords: TV discourse, oral speech, pronounciation norm, phonostylistic levels, codified norm, speech reality
foreign words.